The Role of the As'adiyah Pesantren in Countering Radicalism in Wajo of Indonesia - Nurdin, Nurdin; Hasmulyadi, Hasmulyadi; Hamzah, Ekawati (FIKRAH, 2024)
The radicalism and extremism movement has spread to religious educational institutions, especially in Islamic boarding schools. This research aims to strengthen the As'adiyah Islamic Boarding School community in Wajo Regency which focuses on the role of As'adiyah Islamic Boarding School in promoting moderate Islamic values and Pancasila in facing the challenges of radicalism, as well as strategies carried out by Islamic boarding schools to prevent the spread of radical ideas among students and the surrounding community. This article uses a qualitative approach with observation, interview, questionnaire, and documentation techniques to collect data. The results of the study show that the spread of radical ideas in the pesantren environment and the community is still a significant challenge, with indications that some students are exposed to radicalism and extremism. As'adiyah Islamic Boarding Schools have great potential in encouraging the creation of religious harmony and building a tolerant and peaceful society. This article contributes science in providing insights that are a reference for the government and the community to empower pesantren as a fortress of moderation and a tool to prevent radicalism at the local and national levels.